(Meta)verse as the next escaper from competition public enforcement - Luca Megale (Market and Competition Law Review)
While authorities discovered the need to regulate competition in the digital world, one of the Big Techs – Facebook – changed its name in Meta. The latter emphasizes the shift from being a social network company to becoming a metaverse one. The paper argues that a new digital world is laying its foundations, and competition public enforcement risks being caught off-guard again. Such a new world is based on the concepts of metaverse, web3 and the tools of algorithms and blockchain. The common element is decentralization; however, in the hand of a few main characters governing the sector as it is today – not the users. Therefore, public competition enforcement will have today’s criticalities, yet heavily amplified by the characteristics of the metaverse. The paper addresses the potential impact of the metaverse on competition; starting from the essential facility doctrine, the application of its elements to the metaverse can only be hypothesized. However, it is noted that, in a worst-case scenario, the requirements would be met with some amendments (given by the nature of the new market). Moving on, it is asserted as tacit collusion might be a crucial issue due to algorithms and blockchain. Metaverse might also be characterized by repeating concerns. Regulators’ lack of attention on M&A review had a crucial role in the development of the present digital markets. The latter was the consequence of regulators not understanding the potential future outcome of acquisitions and impact on markets. This might already be happening again. Lastly, the metaverse could not only increase the data gathered by undertakings, but also their quality, thanks to the use of new technologies. Thus, amplifyingthe ability of predicting consumers’ behaviour and undertakings’ market power (to be added to the already present concerns on data exploitation). To front this scenario, competition public enforcement, as it is today, might not be enough. The paper claims that a regulatory intervention is needed to avoid history repeating itself: while regulators have no clear idea on what and how to regulate the digital platforms, Big Techs continue their power climbing. In a still unknown metaverse infrastructure, what is needed is a future-oriented analysis of the problem drivers and scenarios. Therefore, the proposed approach varies based on the specific antitrust concern. The common word is regulatory foresight; however, it must also be considered that a lack of uniformity between Countries – even EU Member States –, and the current hard adaptability of antitrust norms and doctrines (e.g., essential facilities), risk to hamper a needed regulatory adaptability.